Integration of facility management and building information modeling (BIM): A review of key issues and challenges. Issue 7 (7th May 2019) - Dixit, Manish K.; Venkatraj, Varusha; Ostadalimakhmalbaf, Mohammadreza; Pariafsai, Fatemeh; Lavy, Sarel
Abstract : Purpose: The purpose of this study is to investigate factors that impede the integration of facilities management (FM) into building information modeling (BIM) technology. The use of BIM technology in the commercial construction industry has grown enormously in recent years. Its application to FM, however, is still limited. The literature highlights issues that hinder BIM–FM integration, which are studied and discussed in detail in this paper. Design/methodology/approach: A review of literature is conducted to identify and categorize key issues hampering the application of BIM to FM. This paper has also designed a questionnaire based on a literature review and surveyed FM professionals at two industry events. Using the collected responses, these issues are analyzed and discussed using non-parametric statistical analyses. Findings: A total of 16 issues are identified through the literature review of 54 studies under the four categories of BIM-execution and information-management, technological, cost-based and legal and contractual issues. The results of the survey of FM professionals (with 57 complete responses) reveal that the single most important issue is the lack of FM involvement in project phases when BIM is evolving. Originality/value: The findings of this study could assist the construction industry (e.g. building-material and equipment manufacturers, design professionals, general contractors, construction managers, owners and facility managers) with creating guidelines that would help in BIM–FM integration. BIM is a virtual database that contains important design and construction information, which can be used for effective and efficient life cycle management if building data are captured completely and accurately with a facility manager's involvement.